GOOD CORPORATE GOVERNANCE DAN DAMPAKNYA TERHADAP KINERJA BERDASARKAN BALANCED SCORECARD - Dewi Fitriyani; Wiwik Tiswiyanti; Eko Prasetyo (Jurnal Akuntansi, 2016)
The aims of the study were to describe the practice of good corporate governance, to measure performance on PDAM with balanced scorecard, and to find out the correlation between the practice of good corporate governance to performance. This study conducted on five PDAM in Jambi Province. Collection of data obtained through interviews, questionnare, annual report, related of documents and policies. The results of this study indicate good corporate governance practices on PDAM in Jambi Province in pretty good kriteria. PDAM performance scores as measured by balanced scorecard show overall is still considered less than the target maksimum working. The result of Pearson Product Moment test show the correlation between good corporate governance practices with the performance has a strong relationship but not significant.